Politik Hukum Dalam Penanganan Covid-19: Pendekatan Yuridis Dalam Sistem Hukum Indonesia - Ahmad Gelora Mahardika (Fakultas Hukum Universitas Islam Malang, 2022)
The condition of the economic and health dilemma in handling covid-19 is due to regulations in the Indonesian legal system forcing the Government to choose to sacrifice one of them. However, the compromising legal politics carried out by the Government has a tendency to deviate from the applicable law. Therefore, a new legal policy is needed in handling the covid-19 pandemic outbreak, including the issuance of a PERPU as legitimacy to provide legal certainty for a number of policies carried out by the Government that deviate from the applicable laws and regulations. The research method in this article is normative juridical. The issuance of PERPU is the most appropriate legal policy to overcome problems related to the covid-19 pandemic which is trapped between economic and health dilemmas.